gwp 2014
DOI: 10.24149/gwp178
|View full text |Cite
|
Sign up to set email alerts
|

Credit Booms, Banking Crises, and the Current Account

Abstract: A number of papers have shown that rapid growth in private sector credit is a strong predictor of a banking crisis. This paper will ask if credit growth is itself the cause of a crisis, or is it the combination of credit growth and external deficits? This paper estimates a probabilistic model to find the marginal effect of private sector credit growth on the probability of a banking crisis. The model contains an interaction term between credit growth and the level of the current account, so the marginal effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
1
19
0
2
Order By: Relevance
“…Such capital inflows may lead to stock market bubbles and the excessive expansion of domestic credit and may cause inflationary pressures (Calvo et al 1994;Caballero 2014). Davis et al (2016) find that an increase in debt matters for the outbreak of a crisis especially if the current account deficit of a country is large. We use the change in the real value of the current account as a measure of international capital flows.…”
Section: Predictors Of Financial Crisesmentioning
confidence: 88%
See 1 more Smart Citation
“…Such capital inflows may lead to stock market bubbles and the excessive expansion of domestic credit and may cause inflationary pressures (Calvo et al 1994;Caballero 2014). Davis et al (2016) find that an increase in debt matters for the outbreak of a crisis especially if the current account deficit of a country is large. We use the change in the real value of the current account as a measure of international capital flows.…”
Section: Predictors Of Financial Crisesmentioning
confidence: 88%
“…We also add a dummy variable indicating when a deposit insurance scheme was introduced. 2 In each step of our empir- 1 In addition to income inequality and credit booms, other factors that have been proposed to explain the occurrence of financial crises include collapses of asset bubbles, deregulation, financial innovations, movements of real interest rates, deposit insurance schemes, the growth of the monetary base, and current account imbalances (see Gorton (1988); Calvo et al (1994); Stoker (1994); Demirgüc-Kunt and Detragiache (1998); Brunnermeier (2008); Tett (2009); In't Veld et al (2011); Davis et al (2016)). 2 We experimented also with a dummy variable indicating the existence of a central bank, but it failed to ical analysis, we then apply a general-to-specific model selection procedure to obtain the most parsimonious choice of variables that provides the most predictive information on the probability of a financial crisis.…”
Section: Introductionmentioning
confidence: 99%
“…DellAriccia and Marquez (2006) suggest that banks have lowered their lending standards during periods of rapid credit growth, which in turn worsened the credit portfolio and the banking system became vulnerable to financial pressure as downside risks to the economy arise. Jorda, et al (2011), Davis, et al (2016) suggest that excessive credit growth is the best indicator of the financial crisis and that this relationship is strengthened when it is combined with the increasing current account deficit. In a similar study, Schularick and Taylor (2009) have argued that successive economic instability is caused by a bad credit growth period.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Studies have shown that credit growth is a strong determinant of banking crisis. Meanwhile, further research has proven that credit growth generated by domestic savings has less negative impact than that generated by foreign borrowing, and this has been seen to be more dangerous in countries without capital account restrictions [15]. Also, found that private sector credit is a significant predictor of systemic financial risk [16].…”
Section: Introductionmentioning
confidence: 99%
“…The same pattern replicated when they extended the sample to 54 advanced and emerging economies. In a similar study, [15] applied probabilistic and logit modeling to data from 35 European countries to investigate if credit growth is itself the cause of a banking/financial crisis. Their study revealed that the marginal impact of increasing private sector debt level is dependent on the external debt position of an economy.…”
Section: Introductionmentioning
confidence: 99%